Synthesis and Characterization of Rice Straw Derived Nanoscale Biochar-Based Fertilizer Infused with Nutrients - Ramos, Nerissa C (Archīum Ateneo, 2022)
Biochar research has been gaining recent interest in agricultural applications because of its use as a soil amendment. Biochar is a porous carbonaceous solid produced from heat in the absence of any introduced oxygen (pyrolysis). It has relatively high surface area and slow-release properties that makes it suitable for fertilizer formulation. In this study, rice straw is used for biochar production using modified carbonizer at 600-650o C temperature range. After synthesis in the nanoscale level, the biochar produced was infused with nutrients such as nitrogen, phosphorus, potassium and zinc. The morphological characteristics were studied using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), and energy dispersive Xray spectrometry (EDS). Nutrients were incorporated in the biochar and analysis revealed concentrations of 4.96% N, 3.46% P, 2.25% K, and 10.90% OM. The nanoscale biochar-based fertilizer was then applied into rice production. Rice grown in soil amended with nanoscale biochar-based fertilizer showed higher yield than control treatments but with comparable result from the inorganic fertilizer treatments. This implies that biochar can be used as an alternative to chemical based fertilizer when infused with the essential nutrients needed by plants. Furthermore, the soil amended with the nanoscale biochar-based fertilizer was also found to have a higher nutrient and organic matter content after harvest. Therefore, it could preserve the soil fertility which is beneficial in the long term.